2020
DOI: 10.1021/acs.jpcc.0c06065
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on CO2 Electroreduction Pathways in an Imidazolium-Based Ionic Liquid on Pt Electrode

Abstract: Ionic liquids (ILs) are thermally stable at both high and low temperatures, making them excellent solvents and electrolytes in extreme ambient conditions. In this work, we systematically studied the temperature effects on the various pathways of electrochemical reduction of CO 2 in 1-ethyl-3methylimidazolium bis(trifluoromethylsulfonyl)imide ([Emim]-[NTf 2 ]) and compared them with those in 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([Bmpy][NTf 2 ]) by electrochemical methods and density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Zhan et al [143] fabricated an imidazolium-Pt catalytic system and found that CO 2 RR in ILs is affected by temperature (Fig. 12).…”
Section: Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhan et al [143] fabricated an imidazolium-Pt catalytic system and found that CO 2 RR in ILs is affected by temperature (Fig. 12).…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…CO 2 reduction on the imidazolium-Pt surface at different temperatures. Reproduced with permission from Ref [143]…”
mentioning
confidence: 99%
“…80 Zhan et al showed that the more densely packed EDL of [C 2 mim][TFSI] in an electric field shows a higher capacitance compared to the less densely packed EDL of [C 4 mpyrr][TFSI]. 81 They showed that changes in temperature can alter the behavior of the EDL in the presence of an analyte, such as carbon dioxide (CO 2 ). For the electrochemical reduction of CO 2 in [C 2 mim][TFSI], five different reaction pathways are possible.…”
Section: Effect Of the Edl On Electrochemicalmentioning
confidence: 99%
“…For the electrochemical reduction of CO 2 in [C 2 mim][TFSI], five different reaction pathways are possible. 81 Variations in temperature can therefore be used to tune the reaction pathway because of the alteration of the EDL at the IL/ electrode interface.…”
Section: Effect Of the Edl On Electrochemicalmentioning
confidence: 99%
See 1 more Smart Citation